Crystallization and preliminary X-ray crystallographic analysis of human autotaxin - Inoue, Keigo (International Union of Crystallography, 2011)
Autotaxin (ATX), which is also known as ectonucleotide pyrophosphatase/phosphodiesterase 2 (NPP2 or ENPP2) or phosphodiesterase Iα (PD-Iα), is an extracellular lysophospholipase D which generates lysophosphatidic acid (LPA) from lysophosphatidylcholine (LPC). ATX stimulates tumour-cell migration, angiogenesis and metastasis and is an attractive target for cancer therapy. For crystallographic studies, the α isoform of human ATX was overproduced in Escherichia coli, purified and crystallized using the hanging-drop vapour-diffusion method. X-ray diffraction data were collected to 3.0 Å resolution from a monoclinic crystal form belonging to space group C2, with unit-cell parameters a = 311.4, b = 147.9, c = 176.9 Å, β = 122.6°.